2009
DOI: 10.1292/jvms.71.425
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Leptospira spp. from Raccoons in Japan

Abstract: ABSTRACT. We investigated whether raccoons (Procyon lotor) carried leptospires in their kidneys in Japan. Leptospira was isolated from 2 of 71 raccoons captured in Kanagawa Prefecture and 1 of 53 raccoons at a zoological park in Nagasaki Prefecture. Anti-Leptospira antibodies were detected in 16 of 124 raccoons (12.9%) in Kanagawa and 33 of 53 raccoons (62.3%) in Nagasaki, respectively. The partial nucleotide sequences of their flaB genes suggested that the isolates belonged to L. interrogans. The serovars of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…However, our use of PFGE and gyrB sequence analysis as alternative methods for typing isolates have been done in other studies of leptospirosis. 6,7,22,26,28,29,38,53 The results of our study provide useful information on the epidemiology of leptospirosis in the Philippines, which until now was not well studied. However, studies with larger sample sizes on leptospirosis among rats, humans, and other animals in other areas of the Philippines would be beneficial in determining the transmission cycle of leptospirosis and the status of this zoonosis.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, our use of PFGE and gyrB sequence analysis as alternative methods for typing isolates have been done in other studies of leptospirosis. 6,7,22,26,28,29,38,53 The results of our study provide useful information on the epidemiology of leptospirosis in the Philippines, which until now was not well studied. However, studies with larger sample sizes on leptospirosis among rats, humans, and other animals in other areas of the Philippines would be beneficial in determining the transmission cycle of leptospirosis and the status of this zoonosis.…”
Section: Discussionmentioning
confidence: 89%
“…Pulsed-field gel electrophoresis was carried out based on the method previously described. 28 Briefly, DNA from 1 mL of Leptospira isolates was digested with Not I and subjected to electrophoresis in CHEF DR III (Bio-Rad, Hercules, CA) for 20 hr at 14°C with recirculating 0.5× Tris-borate-EDTA buffer. Electrophoresis conditions included switch times of 10 seconds and 60 seconds for L. interrogans or 10 seconds and 40 seconds for L. borgpetersenii , an angle of 120°, and a gradient of 6 V/cm.…”
Section: Methodsmentioning
confidence: 99%
“…RFLP analysis of the genomes of Leptospira isolates was conducted by PFGE using the restriction enzyme NotI, as described previously (Koizumi et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…Several serologic surveys in the United States demonstrate that raccoons commonly have circulating antibodies to a number of L. interrogans serovars including grippotyphosa, autumnalis, hardjo, and icterohemorrhagiae (Junge et al, 2007;Raizman et al, 2009;Richardson and Gauthier, 2003). Some studies have confirmed nephritis in association with the bacteria by using PCR and immunohistochemistry, indicating that raccoons are susceptible to disease and do not simply serve as asymptomatic reservoirs (Duncan et al, 2012;Hamir et al, 2001;Koizumi et al, 2009). Leptospiral infections have also been reported in mongoose and genets, with L. interrogans serovar icterohemorrhagiae being the most commonly identified strain (Millán et al, 2009;Moinet et al, 2010).…”
Section: Bacteriamentioning
confidence: 99%